The Person and His Development. The Gestalt Approach in Academic Education - Żłobicki, Wiktor (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2020)
The Gestalt approach in education sees human beings and their relation with the world as a single whole. This assumption is a base for methodology of development of human potential. In the article author paid attention to a few topics: many students are unaware of their potential and the educator is thus obliged to reveal it; the process of studying is dynamic; it has its periods of intensity and activity but also slowing down or even coming to a halt; the process of learning takes place not only within the walls of an academic institution, but also more often outside (for example the innovation and ground breaking research occurring in the labs of technology sector); the involvement of students in the development of the curriculum leads to positive results.
Keywords: Gestalt